Rapid Accumulation of Proline Enhances Salinity Tolerance in Australian Wild Rice Oryza australiensis Domin - Ha Thi Thuy Nguyen; Sudipta Das Bhowmik; Hao Long; Yen Cheng; Sagadevan Mundree; Linh Thi My Hoang (Plants, 2021)
Proline has been reported to play an important role in helping plants cope with several stresses, including salinity. This study investigates the relationship between proline accumulation and salt tolerance in an accession of Australian wild rice Oryza australiensis Domin using morphological, physiological, and molecular assessments. Seedlings of O. australiensis wild rice accession JC 2304 and two other cultivated rice Oryza sativa L. cultivars, Nipponbare (salt-sensitive), and Pokkali (salt-tolerant), were screened at 150 mM NaCl for 14 days. The results showed that O. australiensis was able to rapidly accumulate free proline and lower osmotic potential at a very early stage of salt stress compared to cultivated rice. The qRT-PCR result revealed that O. australiensis wild rice JC 2304 activated proline synthesis genes OsP5CS1, OsP5CS2, and OsP5CR and depressed the expression of proline degradation gene OsProDH as early as 1 h after exposure to salinity stress. Wild rice O. australiensis and Pokkali maintained their relative water content and cell membrane integrity during exposure to salinity stress, while the salt-sensitive Nipponbare failed to do so. An analysis of the sodium and potassium contents suggested that O. australiensis wild rice JC 2304 adapted to ionic stress caused by salinity by maintaining a low Na+ content and low Na+/K+ ratio in the shoots and roots. This demonstrates that O. australiensis wild rice may use a rapid accumulation of free proline as a strategy to cope with salinity stress.